2015
DOI: 10.1103/physrevc.92.044302
|View full text |Cite
|
Sign up to set email alerts
|

Preformation probability inside α emitters having different ground state spin-parity than their daughters

Abstract: ABSTRACT:The ground-state spin and parity of a formed daughter in the radioactive -emitter is expected to influence the preformation probability of the  and daughter clusters inside it. We investigate the  and daughter preformation probability inside odd-A and doubly-odd radioactive nuclei when the daughter and parent are of different spin and/or parity. We consider only the ground-state to ground-state unfavored decays. This is to extract precise information about the effect of the difference in the ground… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 45 publications
4
58
0
Order By: Relevance
“…Here, our calculated P 0 values are in tune with the shell model, with notable minima around the magic numbers. This conforms with the recent findings of [24,25], in which it was demonstrated that P 0 can be influenced by the isospin asymmetry of the parents, the deformation of the daughter nuclei, and pairing and shell effects and that the minima of P 0 can be ascribed to the presence of proton, neutron shells and sub-shell closures. A careful evaluation of Figure 6, which portrays the relationship between the preformation probability P 0 and the penetrability P, where both parameters are shown as a function of the mass number, reveals that lower P 0 values correspond to a higher P and vice versa, such that their products P 0 P are near to the same order for all the decay chains under study.…”
Section: Nucleisupporting
confidence: 92%
See 1 more Smart Citation
“…Here, our calculated P 0 values are in tune with the shell model, with notable minima around the magic numbers. This conforms with the recent findings of [24,25], in which it was demonstrated that P 0 can be influenced by the isospin asymmetry of the parents, the deformation of the daughter nuclei, and pairing and shell effects and that the minima of P 0 can be ascribed to the presence of proton, neutron shells and sub-shell closures. A careful evaluation of Figure 6, which portrays the relationship between the preformation probability P 0 and the penetrability P, where both parameters are shown as a function of the mass number, reveals that lower P 0 values correspond to a higher P and vice versa, such that their products P 0 P are near to the same order for all the decay chains under study.…”
Section: Nucleisupporting
confidence: 92%
“…Particularly, some neutron-deficient nuclei around the region Z = 82 in the heavy-ion reaction are often excluded in the in-beam γ-ray experiments [17]. On the other hand, all theoretical probes on this shell closure emanate from either the nuclear fission [18][19][20] or Gamow theory of α-decay [21][22][23][24][25]. The former relegates the idea of preformation; i.e., it is assumed that clusters are formed during the separation/deformation process of the parent nucleus while penetrating the confining interaction barrier.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, α preformation probabilities are usually extracted from rates of experimental α decay half-lives to theoretical results calculated without considering the preformation factors [32][33][34]. Recently a semi-empirical formula of α preformation probabilities taking into account the shell effect, the pairing effect, and the angular momentum effect has been given [35]. Seif et al have proposed that the α preformation probability is proportional to N p N n for even-even nuclei around proton Z = 82, neutron N = 82 and 126 shell closures [36].…”
Section: Introductionmentioning
confidence: 99%
“…The deformations affect strongly the barrier penetration probability [38,39] and indicate the optimum orientations at which the minimum fragmentation potential takes place. As an example, shown in Fig.…”
Section: II R Esu L Ts a N D Discussionmentioning
confidence: 99%